Omissão legislativa e controle de constitucionalidade pelo Supremo Tribunal Federal: problemática entre jurisdição constitucional e democracia - Guimarães, Guilherme da Rosa (2025)
This master's thesis, developed within the research line “State, Jurisdiction, and Social Inclusion,” is part of the UN Sustainable Development Goals, discussing “Peace, Justice, and Effective Institutions.” The work proposes to analyze the performance of the Federal Supreme Court (STF) through constitutional control in the face of legislative omissions. It uses the hypothetical deductive method and bibliographic review to debate whether this performance by the STF has exceeded its limits and violated the principle of separation of powers. In its first chapter, it analyzes the concept of unconstitutional legislative omission, addressing its evolution, differentiation, and conceptual scope up to the present day after the 1988 Federal Constitution. The second chapter focuses on constitutionality control, analyzing possible actions in cases of partial and total omissions, the procedures and instruments applicable in each situation, and the differentiation between Direct Action of Unconstitutionality by Omission and Writ of Injunctions as the main actions in the control of legislative omissions. and, finally, investigates atypical forms of control of omissions when they do not result from the absence of a normative act. Finally, the third and last chapter analyzes the conflict between the STF's role as constitutional guardian in relation to the issues raised above, analyzing its causes and repercussions on the democratic rule of law, concluding, at the end of the research, in a simplified manner, that the STF must always act through the instruments and limits specifically created for the control of omissions, prioritizing as much as possible the preservation of the functions reserved for democratic institutions, in order to avoid undue invasion of the other powers.